Neutron reflectometry from poly (ethylene-glycol) brushes binding anti-PEG antibodies: Evidence of ternary adsorption. (April 2015) - Schneck, Emanuel; Berts, Ida; Halperin, Avraham; Daillant, Jean; Fragneto, Giovanna
Abstract: Neutron reflectometry provides evidence of ternary protein adsorption within polyethylene glycol (PEG) brushes. Anti-PEG Immunoglobulin G antibodies (Abs) binding the methoxy terminated PEG chain segment specifically adsorb onto PEG brushes grafted to lipid monolayers on a solid support. The Abs adsorb at the outer edge of the brush. The thickness and density of the adsorbed Ab layer, as well as its distance from the grafting surface grow with increasing brush density. At high densities most of the protein is excluded from the brush. The results are consistent with an inverted "Y" configuration with the two F AB segments facing the brush. They suggest that increasing the grafting density favors narrowing of the angle between the F AB segments as well as overall orientation of the bound Abs perpendicular to the surface.